Analisis Formalin dalam Sampel Ikan dan Udang Segar dari Pasar Muara Angke - Suryadi, Herman; Kurniadi, Maryati; Melanie, Yuanki (UI Scholars Hub, 2010)
The use of formalin as a food additive has been prohibited by the ministry of health as stipulated in The Indonesia Ministry of Health Regulations No.722/Menkes/Per/IV/88. However, in recent years the Indonesian authorities have found trace amounts of formalin as a preservative in perishable foods such as fish and shrimp. The aim of this research is to identify the use of formalin in fresh fish and shrimp samples sold in Muara Angke Market as the fresh seafood market in Jakarta. The first step of this research was formalin identification in fish and shrimp samples and continued by quantitative analysis to assure the results obtained. Qualitative determination of formalin was carried out by Schryver reagent and the quantitative determination was carried out pectrophotometrically using Nash reagent. Validation of UV-Vis spectrophotometric method for determination of formalin showed that Nash reagent was suitable to determine formalin. The limit of detection, limit of quantitation, and coefficient of variation for formalin were 0,0102 mg/L, 0,0341 mg/L, and 0,09%, respectively. Recovery of formalin in fish samples was 89,79-109,58% and shrimp samples was 82,11-97,76%. Qualitative determination in six fish samples and six shrimp samples showed negative results and the quantitative analysis confirmed that formalin was not found in the fresh fish and shrimp samples from Muara Angke Market.